Encountering—An uncomfortable vocation of love. Theology and practice in Scandinavian parish work. Issue 1 (31st March 2021) - Nahnfeldt, Dr Cecilia
Abstract: This is an analysis of practical theology in a parish, responding to organized racism in the local area. The involvement in civil action, as well as the theological aspects of such work are considered and discussed in relation to Scandinavian creation theology. The need for radical practice is discussed in relation to vocation and the love of the neighbor, even when such practice becomes uncomfortable and even threatening.